Proceedings of the Provincial Consultation Workshop on Food and Agriculture System Transformation in Nepal - Pradhan, Mamata; Palikhe, Aruna; Maharajan, Nanda; Adhikari, Madan; Pandey, Meena; Gupta, Shalini; Mohan, Anisha (International Food Policy Research Institute, 2023)
The United States Government’s (USG) Global Food Security Strategy (GFSS) is an integrated whole-of-government approach that aims to end global hunger, poverty, and malnutrition through the Feed the Future initiative. Launched in 2010 across Africa, Asia, Latin America, and the Caribbean, Feed the Future aims to stimulate agriculture-led growth, resilience, and nutrition in countries with significant needs and opportunities for improvement. Through partnerships that invest in agriculture, build resilience, and improve nutrition, the USG has provided the basic dignity of food to millions of families worldwide. This initiative has delivered impressive results, including an estimated 23.4 million people lifted to above the poverty line, 3.4 million children no longer stunted, and an estimated 5.2 million families overcoming hunger. Additionally, Feed the Future has unlocked $3.5 billion in financing for food security (2011–2019), generated $13.7 billion in agricultural sales, and developed and deployed over 1,000 innovations. However, the Coronavirus disease 2019 (COVID-19) pandemic, climate change, and international conflicts have significantly hampered the achievement of Sustainable Development Goals (SDGs). As a result, the USG has developed the Global Food Security Strategy Refresh (GFSS-R) 2022–2026 that emphasizes the following five new areas of focus: 1. Equity and inclusion 2. An ambitious approach to climate change 3. Countering the long-term impacts of COVID-19 4. Employing systems thinking and working across the food system 5. Integration of conflict management, peacebuilding, and social cohesion This strategy refresh has significant implications for the Feed the Future initiative; therefore, all Feed the Future countries have now embarked on refreshing the country strategy to incorporate new programs and initiatives aligning with the GFSS-R. The strategy involves implementing a multi-faceted whole-of-government approach, assignment of ownership, and empowerment of country leadership to lead and guide the efforts for progress. The strategy refresh invokes partnership with a wide range of stakeholders, and harnesses the advancement of science, technology, and innovation to achieve these objectives. The Feed the Future interventions in Nepal ensured a very close partnership with the Government of Nepal and emphasized greater involvement of the private sector. Nepal is one of the oldest and most successful Feed the Future countries. Although efforts have been made to ensure food security in Nepal, the country still faces nutritional deficiency. Agricultural productivity in Nepal is comparatively low, and most of the farmers are still engaged in subsistence farming. Further, Nepal is highly vulnerable to climate change, natural disasters, pests, and diseases, exacerbating food insecurity leading to the prevalence of nutrition deficiencies, especially among marginalized populations who rely heavily on agriculture for their livelihoods. The USAID mission in Nepal commissioned the IFPRI to support the drafting of the new GFSS Nepal Country Plan. In this regard, provincial consultation workshop has been planned in collaboration with IIDS to generate constructive ideas and feedback on the past and existing interventions implemented in Nepal under Feed the Future and identify a way forward for strengthening and leveraging food and agriculture system transformation in Nepal.